Urban development in Kenya :towards inclusive cities - (:unkn) unknown (My University, 2008)
With an urban growth of 4% and an urban population of more than 30% (Vision 2030), one out of every two Kenyans will live in urban areas before 2030 (and probably by 2015). As urbanization is inevitable, the main challenge is how to cope with rapid urban growth and how to prepare for the future. Inclusive development is a major condition of sustainable cities. What are the main urban challenges Kenya faces? Are Kenyan urbanization trends leading to inclusive cities? Urban challenges in Kenya Urban growth challenging service delivery In terms of urbanization patterns, Nairobi continues to be the major city while other big towns remain attractive for rural migrants. However, small and secondary towns (20 to 200 000 inhabitants) are now growing faster. An important factor in the growth of small and secondary towns is the extension of big cities' metropolitan areas. They can no longer be neglected by development programmes. Balanced urbanization will also require Provincial capitals to play a role as regional hubs. Therefore, their capacities urgently need to be strengthened. Urban growth, combined with urban sprawl, has overwhelmed the capacity of local authorities to provide the population with adequate urban facilities. Only around 30% of urban dwellers have access to a private water connection and the rest rely on public standpipes or other sources. Sanitation lags further behind, with 44% of the facilities being pit latrines. Garbage collection is another challenge, with a general lack of waste disposal and treatment facilities. Housing and informal settlements
Keywords: African Research